2003
DOI: 10.33584/jnzg.2003.65.2527
|View full text |Cite
|
Sign up to set email alerts
|

Integrating novel forage management into sheep farm systems

Abstract: Sheep have a higher intake of nutrients when offered continuous free access to ryegrass and white clover growing separately than when offered the same species growing as a mixture. To determine if this greater nutrient intake would translate to higher animal performance, three experiments of 3-6 weeks duration measured liveweight gain by ewes+twin lambs in early spring, weaned lambs in mid-late spring and hoggets during late winter to identify the class of sheep most responsive to this form of forage presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Cosgrove et al (2003) used a farm system model to determine if the greater nutrient intake possible from a spatially separated clover–grass mixture would translate to better whole‐farm performance outcomes. They compared scenarios where proportions of 0, 0.05, 0.1, 0.15, or 0.2 of the available grazing area were sown to spatially separated swards and predicted that growing this pasture type on 0.15 to 0.2 of a typical sheep breeding and finishing farm in North Island, New Zealand, could increase total lamb carcass output and net farm profit.…”
Section: Animal Production Responses To Controlled Spatial Variabilitmentioning
confidence: 99%
“…Cosgrove et al (2003) used a farm system model to determine if the greater nutrient intake possible from a spatially separated clover–grass mixture would translate to better whole‐farm performance outcomes. They compared scenarios where proportions of 0, 0.05, 0.1, 0.15, or 0.2 of the available grazing area were sown to spatially separated swards and predicted that growing this pasture type on 0.15 to 0.2 of a typical sheep breeding and finishing farm in North Island, New Zealand, could increase total lamb carcass output and net farm profit.…”
Section: Animal Production Responses To Controlled Spatial Variabilitmentioning
confidence: 99%
“…() and <35 days for Cosgrove et al . (). Continuous stocking may lead to clover being depleted and not able to contribute significantly to the quality of feed offered.…”
Section: Discussionmentioning
confidence: 97%
“…They are also contrary to Cosgrove et al . (), who showed that liveweight gain of sheep was greater on spatially separated monocultures than mixtures. The dissimilarity between the findings of this study and those of previous studies may reflect the difference in the duration of the study, being 8 days for Champion et al .…”
Section: Discussionmentioning
confidence: 99%
“…The low preference of deer for ryegrass, yet the ryegrass dominance in deer grazed swards, is evidence to support this principle. Recent studies with sheep (Cosgrove et al 2001 and dairy cows (Marotti et al 2001) have demonstrated the possibility for a novel management system of growing grass and clover separately instead of as an intermingled mix, and giving them the opportunity to freely choose. To our knowledge this has not been tried with deer, but providing the opportunity for them to easily combine their preference for a mixed diet and a high proportion of clover, with a high total daily intake, might benefit performance just as it does for sheep and cattle.…”
Section: Nutritional and Behavioural Aspects Of Selectionmentioning
confidence: 99%